Organic Transdermal Iontophoresis Patch with Built‐in Biofuel Cell. Issue 4 (17th November 2014) - Ogawa, Yudai; Kato, Koichiro; Miyake, Takeo; Nagamine, Kuniaki; Ofuji, Takuya; Yoshino, Syuhei; Nishizawa, Matsuhiko
Abstract : A completely organic iontophoresis patch is reported. A built‐in biofuel cell is mounted on the patch that generates transdermal iontophoretic administration of compounds into the skin. The amplitude of transdermal current is tuned by integrating a conducting polymer‐based stretchable resistor of predetermined resistance.